Viver e pertencer : identidades e territórios nos assentamentos rurais de Sergipe - Dourado, Auceia Matos (2014)
The creation of rural settlement in Brazil is a historical and relational process, a conquest and produced space that the symbolic and functional appropriation is turned into territory. The main objective of this thesis is to analyze the referential that guides the construction of a territorial identity in rural settlements in Sergipe, to obtain multiples configurations of themselves. It was delimited as locus of investigation five of twenty two settlements, and classified by INCRA in phase seven, that the body corresponds to the consolidated settlements. The methodological way used was the qualitative research, based in three points: the construction of the territory, the meaning of territory and the settlement as a space of reference and the sense of being settled. This research was developed in transversal levels of characterization and analysis. A discussion was held about the territory category and its characteristics to comprehend the rural settlements, considered as territories, product and conditions of fights territorialization for lands in Brazil. The agrarian problem in Brazil and Sergipe was analyzed in a way to contextualize the object of study and the settlements studied was taken as a space of experience and reference to comprehend their identities. The delimitation of this research was guided from the comprehension that the construction of identities and territorialities in settlements is historical and relational, because the settled ones build social relations and establish link. The sense of being settled reveals itself as institutional and symbolic content and means not only a territorial category, but also the construction of social and spatial consciousness, that expresses in traditions and translations. This is the process of identity construction in settlements. A dialect that includes functionality and symbology, memory and daily routine, symbols and marks, objectivity and subjectivity.